1996
DOI: 10.1093/hmg/5.5.645
|View full text |Cite
|
Sign up to set email alerts
|

Crigler-Najjar syndrome type II is inherited both as a dominant and as a recessive trait

Abstract: Crigler-Najjar syndrome type II (CN-II) is caused by a severely reduced hepatic activity of bilirubin UDP-glucuronosyltransferase (UGT). Recently, by the analysis of the genetic background of CN-II patients, it has been clarified that the patients carry homozygous missense mutations or nonsense plus missense mutations on the gene for UGT, and CN-II was inherited as an autosomal recessive trait. We encountered a new case which had a nonsense mutation caused by a single nucleotide substitution on one allele. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…Gene analyses have shown both patients having recessive traits with homozygous missense mutations and a patient having dominant traits with a heterozygous nonsense mutation (Aono et al 1993;Bosma et al 1993;Koiwai et al 1996). In our study, inheritance in patients 2-7 was recessive, in agreement with findings reported earlier; however, patient 1 appears to show complicated inheritance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Gene analyses have shown both patients having recessive traits with homozygous missense mutations and a patient having dominant traits with a heterozygous nonsense mutation (Aono et al 1993;Bosma et al 1993;Koiwai et al 1996). In our study, inheritance in patients 2-7 was recessive, in agreement with findings reported earlier; however, patient 1 appears to show complicated inheritance.…”
Section: Discussionsupporting
confidence: 92%
“…In recent studies on mutation analysis of patients with CN type II, five types of mutations which exist exclusively in the coding region have been reported: a single homozygous missense mutation (Arg209Trp) (Bosma et al 1993), a single homozygous missense mutation (Gln331Arg) (Moghrabi et al 1993), double homozygous missense mutations (Gly71Arg and Tyr486Asp) (Aono et al 1993), heterozygous missense (Leu175Glu) and frame shift mutations (Seppen et al 1994), and a single heterozygous nonsense mutation (Gln331Stop) (Koiwai et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that genetic factors are involved in the development of neonatal hyperbilirubinemia. Recently, homozygous A(TA) 7 TAA variation in promoter of UGT1A1 gene was found to be associated with neonatal hyperbilirubinemia in Sephardic Jews (10), Americans (11), Italians (12,13), and British (14). However, in Japanese studies, the high allele-frequency of Gly71Arg in UGT1A1 gene was found to be responsible for neonatal hyperbilirubinemia without obvious cause (15,16).…”
mentioning
confidence: 99%
“…Very recently, we used the technique of PCR to determine the UGT1A1 gene in Taiwan Chinese adults and found that the occurrence of A(TA) 7 TAA allele was relatively rare (14.3% versus 40%) and the variation rate within the coding region was much higher (29.3% versus 0.1%) in Taiwan Chinese compared with Caucasians (17). In addition, we found a novel compound heterozygous variation within the coding region of the UGT1A1 gene that caused CN 2 in an adult patient (18).…”
mentioning
confidence: 99%
“…10,18) It has been suggested that Gilbert's syndrome comes from a dominant negative phenomenon by oligomerization composed of inactive monomer mutants. 19) In guinea pigs, the dimer of UGT is more active for morphine metabolism. 17) Opioid drugs are metabolized by UGT in liver, and morphine is metabolized by hUGT2B7 to the major product, morphine-3-glucoronide (M3G), and the minor product, morphine-6-glucuronide (M6G).…”
Section: Introductionmentioning
confidence: 99%